Circular RNA ERBIN Promotes Proliferation of Hepatocellular Carcinoma via the miR-1263/CDK6 Axis - Yang, Shikun; Yu, Fei; Ji, Yang; Shen, Yanjun; Lu, Hao; Gao, Yuan; Zhang, Feng; Wang, Xuehao; Zhang, Chuanyong (Frontiers in Oncology, 2022)
Objectives: Hepatocellular carcinoma (HCC) is the most common primary liver cancer with high aggressiveness and extremely poor prognosis. Increasing evidence has suggested that circular RNAs (circRNAs), characterized by high stability, play a crucial role in multiple malignancies progression. However, the role of circRNAs in HCC remains elusive. Materials and Methods: The expression of circRNAs in HCC was identified by qRT-PCR. A series of functional experiments both in vivo and vitro were used to determine the role of circERBIN in HCC proliferation. Bioinformatics analysis and RNA pulldown assays were used to explore the downstream target of circERBIN. Results: Here, the expression of circERBIN was demonstrated upregulated in HCC cell lines and tissues and high circERBIN expression levels predicted poor prognosis in HCC patients. Elevated circERBIN promoted HCC cell cycle G1/S transition, thus facilitating HCC cells proliferation and tumorigenesis. Mechanistic investigation revealed that circERBIN regulated HCC proliferation by acting as the sponges of miR-1263, which subsequently targeted cyclin dependent kinase 6(CDK6) and controlled cell cycle G1/S transition. Conclusion: Taken together, our results determined that circERBIN functioned as an important epigenetic regulator in HCC development, highlighting that circERBIN may be a promising target in HCC treatment.